2017
DOI: 10.3389/fphar.2017.00791
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Liver Injury of Polygonum multiflorum Thunb. in Rats by Metabolomics and Traditional Approaches

Abstract: Liver injury induced by Polygonum multiflorum Thunb. (PM) have been reported since 2006, which aroused widespread concern. However, the toxicity mechanism of PM liver injury remained unclear. In this study, the mechanism of liver injury induced by different doses of PM after long-term administration was investigated in rats by metabolomics and traditional approaches. Rats were randomly divided into control group and PM groups. PM groups were oral administered PM of low (10 g/kg), medium (20 g/kg), high (40 g/k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 46 publications
2
20
0
Order By: Relevance
“…In this study, the increased concentration of AST and ALT represented severe liver injury, in addition, the increased concentration of UA, UREA, CREA, and TBA represented severe kidney injury, which correlates with other studies (Al-Hashem et al 2019; Jeong et al 2015; Waters et al 2005). We also found the decreased concentration of TP and increased concentration of ALP, which indicated liver disease (Li et al 2017). The levels of rat serum ALT, AST, and ALP exposed to 200 mg/Kg TAA and 400 mg/Kg TAA group were signi cantly increased, which indicated that the liver cell membrane was impaired and the release of them into blood was increased after TAA administration.…”
Section: Discussionsupporting
confidence: 91%
“…In this study, the increased concentration of AST and ALT represented severe liver injury, in addition, the increased concentration of UA, UREA, CREA, and TBA represented severe kidney injury, which correlates with other studies (Al-Hashem et al 2019; Jeong et al 2015; Waters et al 2005). We also found the decreased concentration of TP and increased concentration of ALP, which indicated liver disease (Li et al 2017). The levels of rat serum ALT, AST, and ALP exposed to 200 mg/Kg TAA and 400 mg/Kg TAA group were signi cantly increased, which indicated that the liver cell membrane was impaired and the release of them into blood was increased after TAA administration.…”
Section: Discussionsupporting
confidence: 91%
“…Unfortunately, no satisfactory biomarkers are currently available to identify human populations susceptible to this injury. Moreover, conventional animal models in which only high doses that significantly exceed the typical PM dose that can induce liver injury are not suitable for mimicking dose‐independent, PM‐induced idiosyncratic hepatotoxicity. Recently, however, a rat model of immune action–mediated liver injury induced by cotreatment with a nontoxic dose of lipopolysaccharide and a therapeutic dose of PM exhibited liver injury characteristics similar to those shown in humans and induced a state of immune activation and inflammatory stress .…”
Section: Discussionmentioning
confidence: 99%
“…Liver injury caused by green tea extracts shows dose dependent features but diagnostic biomarkers were not described [67]. Dose dependency can be assumed for HILI caused by phytochemicals derived from germander (Teucrium chamaedris) [17,[75][76][77][78][79], Polygonum multiflorum [68,69,80,81], and plants containing unsaturated pyrrolizidine alkaloids (PAs) [15,[82][83][84][85][86][87][88][89][90]. For these herbs, diagnostic biomarkers are known and in clinical use although test validation was rarely provided [17].…”
Section: Diagnostic Biomarkersmentioning
confidence: 99%
“…In experimental liver injury by Polygonum multiflorum, nine biomarkers were identified using a pathway analysis, which indicated some metabolic involvement of pathways related to lipids, amino acids, and bile acids, but this was not evaluated in patients with liver injury [81]. In clinical studies using prospectively RUCAM for causality assessment in patients with HILI caused by Polygonum multiflorum, a sophisticated but complex evidence chain-based causality identification algorithm was used that also included metabolomics analyses [68].…”
Section: Diagnostic Biomarkersmentioning
confidence: 99%
See 1 more Smart Citation